You are on page 1of 10

Chapter 11 Locus Problems 169

CHAPTER 11 (e) Let P be (x, y).

Exercise 11A (p.275) PA2 − PB2 = 18


( x − 2)2 + ( y + 1)2 − ( x − 5)2 − ( y − 2)2 = 18
1. Let P be (x, y).
x 2 − 4 x + 4 + y2 + 2 y + 1
PA = 3
− ( x 2 − 10 x + 25 + y 2 − 4 y + 4) = 18
( x − 1)2 + ( y − 5)2 = 3
6 x + 6 y − 42 = 0
x 2 − 2 x + 1 + y 2 − 10 y + 25 = 9 x+y−7=0
x 2 + y 2 − 2 x − 10 y + 17 = 0
(f) Let P be (x, y).

2. (a) Let P be (x, y). 2 −1


1 5 2
PA = PB =3
2 x y
( x − 2)2 + ( y + 1)2 = ( x − 5)2 + ( y − 2)2 2 −1
1
x 2 − 4 x + 4 + y2 + 2 y + 1 ( 4 + 5 y − x + 5 − 2 x − 2 y) = ±3
2
= x 2 − 10 x + 25 + y 2 − 4 y + 4 −3 x + 3 y + 9 = ±6
− x + y + 3 = ±2
6 x + 6 y − 24 = 0
x+y−4=0 − x + y + 3 = 2 or − x + y + 3 = − 2
x − y − 1 = 0 or x−y−5=0
(b) Let P be (x, y).
PA = 2 PB 3. Let P be (x, y). The distances from P to the given
x+y x−y
( x − 2)2 + ( y + 1)2 = 2 ( x − 5)2 + ( y − 2)2 lines are and .
2 2
x 2 − 4 x + 4 + y2 + 2 y + 1 x+y x−y
∴ =3
= 4( x 2 − 10 x + 25 + y 2 − 4 y + 4) 2 2
( x + y)( x − y)
3 x 2 + 3 y 2 − 36 x − 18 y + 111 = 0 = ±3
2
x 2 + y 2 − 12 x − 6 y + 37 = 0 x 2 − y 2 = ±6
(c) Let P be (x, y). x 2 − y 2 = 6 or x 2 − y 2 = −6
(Slope of PA)(Slope of PB) = −1
y +1 y − 2 4. Let P be (x, y).
( )( ) = −1
x−2 x−5 x−2
( y + 1)( y − 2) = − ( x − 2)( x − 5) ( x − 4)2 + ( y − 2)2 =
1
y 2 − y − 2 + x 2 − 7 x + 10 = 0 x − 8 x + 16 + y − 4 y + 4 = x − 4 x + 4
2 2 2

x 2 + y2 − 7x − y + 8 = 0 y 2 − 4 x − 4 y + 16 = 0

(d) Let P be (x, y).


5. Let P be (x, y).
PA2 + PB2 = 16
7x − y + 9 x + y −1
( x − 2)2 + ( y + 1)2 + ( x − 5)2 + ( y − 2)2 = 16 =
5 2 2
x 2 − 4 x + 4 + y2 7 x − y + 9 = ±(5 x + 5 y − 5)
+ 2 y + 1 + x 2 − 10 x + 25 + y 2 − 4 y + 4 = 16 7x − y + 9 or 7 x − y + 9
= 5x + 5y − 5 = −5 x − 5 y + 5
2 x 2 + 2 y 2 − 14 x − 2 y + 18 = 0
2 x − 6 y + 14 = 0 or 12 x + 4 y + 4 = 0
x 2 + y2 − 7x − y + 9 = 0 x − 3 y + 7 = 0 or 3x + y + 1 = 0
170 Chapter 11 Locus Problems

6. Let P be (x, y). ( x + 4)2 + y 2


(Slope of PA)(Slope of PB) = −1
= 100 − 20 ( x − 4)2 + y 2 + ( x − 4)2 + y 2
y −1 y − 3
( )( ) = −1 16 x − 100 = −20 ( x − 4)2 + y 2
x+2 x−4
( y − 1)( y − 3) = − ( x + 2)( x − 4) 4 x − 25 = −5 ( x − 4)2 + y 2
y − 4y + 3 + x − 2x − 8 = 0
2 2
( 4 x − 25)2 = 25[( x − 4)2 + y 2 ]
x + y − 2x − 4y − 5 = 0
2 2
16 x 2 − 200 x + 625 = 25( x 2 − 8 x + 16 + y 2 )
9 x 2 + 25 y 2 = 225
7. Let P be (x, y).
A is ( x, 0) , B is (0, y) .
Exercise 11B (p.278)
AB = 6
1. Let P(x, y) be a point on the locus,
x 2 + y2 = 6
Q( x 1, y 1 ) be a variable point.
x 2 + y 2 = 36
∴ 3 x 1 + 4 y 1+ 5 = 0 .........(*)
x y
8. Let the equation of segment be + = 1, then x1 − 2
a b x=
2 3 2
+ = 1. x1 = 2 x + 2 .................(1)
a b
1 1 y1 + 4
Let P(x, y) be the mid-point, then x = a , y = b. y=
2 2 2
2 3 y1 = 2 y − 4 .................(2)
∴ + =1
2x 2y Substitute (1) and (2) into (*),
3 x + 2 y = 2 xy 3(2 x + 2) + 4(2 y − 4) + 5 = 0
3 x − 2 xy + 2 y = 0 6 x + 8y − 5 = 0

9. Let A(a, 0) and B(0, b) be the end-points of the 2. Let P(x, y) be a point on the locus,
line segment, then a 2 + b 2 = 36 . x y
then the mid-point of OP is ( , ) .
Let P(x, y) be the trisection point. 2 2
2 1 Since the mid-point of OP lies on 4 x 2 + y 2 = 4 ,
x= a, y = b the coordinates of this point satisfy the equation.
3 3
3x 2 x y
∴ ( ) + (3 y)2 = 36 4( ) 2 + ( ) 2 = 4
2 2 2
x 2 + 4 y 2 = 16 2 1 2
x + y =4
4
10. Let P be (x, y). 4 x 2 + y 2 = 16

2x + y − 9 x − 2y + 3 3. Let M be ( x 1, y 1 ) , N be (0, y 2 ) , P be (x, y).


=2
5 5 1
2 x + y − 9 = ±( 2 x − 4 y + 6) y = y1 = y 2 , x = x 1 .
3
2x + y − 9 or 2 x + y − 9 y 12 = 12 x 1
= 2x − 4y + 6 = −2 x + 4 y − 6
y 2 = 12(3 x )
5 y − 15 = 0 or 4 x − 3 y − 3 = 0
y−3= 0 y 2 = 36 x

11. Let P be (x, y). 4. Let P be (x, y), Q be ( x 1, y 1 ) ,


PA + PB = 10 then x 1 y 1= 4 .....................(2)

( x + 4)2 + y 2 + ( x − 4)2 + y 2 = 10 Q PQ : OQ = 1 : 2
2 2
( x + 4)2 + y 2 = 10 − ( x − 4)2 + y 2 ∴ x1 = x , y1 = y ,
3 3
Chapter 11 Locus Problems 171

2 2 8. Let P be ( x 1, y 1 ) , Q be ( x 2 , y 2 ) and M(x, y) be


Substitute into (1), ( x )( y) = 4
3 3 the mid-point.
xy = 9 y12 = 8 x1 2 x2 − y2 − 5 = 0
1 2 1
5. Let the slope of BC be m, then the equation of BC x1 = y1 x2 = ( y2 + 5)
8 2
is
PMQ is parallel to x-axis, ∴ y = y1 = y2
y − 1 = m( x + 4 ) 1 1 1 1
y = m( x + 4 ) + 1 x = ( x1 + x2 ) = [ y 2 + ( y + 5)]
2 2 8 2
When x = 0 , y = 1 + 4 m 16 x = y 2 + 4 y + 20
∴ B is (0, 1 + 4 m) . ( y + 2)2 = 16( x − 1)
Let A be (h, 0), then
(Slope of AB)(Slope of BC) = −1 9. Let m be the slope of the line.
4m + 1  y = m( x − 1) ...............(1)
(− )( m) = −1  2
h  y = 4 x ......................(2)
h = ( 4 m + 1)m
Substitute (1) into (2),
Let P be (x, y), then
m 2 ( x − 1)2 = 4 x
1 1
x = (h + 0) , y = (0 + 1 + 4 m) m 2 x 2 − 2( m 2 + 2 ) x + m 2 = 0
2 2
( 4 m + 1)m 1 + 4m Let P(x, y) be the mid-point.
x= , y=
2 2 1
x = (sum of the roots)
x 2
∴ m=
y m2 + 2
1 =
y = ( 4 m + 1) m2
2 2
1 x x = 1 + 2 ...................(3)
= ( 4 ⋅ + 1) m
2 y
y
2 y2 − y = 4 x From(1), m = ......(4)
x −1
Substitute (4) into (3),
6. Let P(x, y) be the mid-point of MN, and H be x −1 2
x = 1 + 2( )
( x 1, y1 ) , y
1 1 y 2 ( x − 1) = 2( x − 1)2
then x = x1 , y = y1
2 2 y 2 = 2( x − 1)
x12 − y12 = 4
(2 x ) − (2 y) 2 = 4
2
10. Let H be (4s, 3s), K be (4t, −3t).
x 2 − y2 = 1 3s + 3t 3 s + t
Slope of HK = = ⋅
4 s − 4t 4 s − t
7. Let P(x, y) be a point on the locus. 3s
It also equals .
4s − 5
2x − y 3 s+t 3s
PM = , PN = y ∴ ⋅ =
5 4 s − t 4s − 5
( s + t )( 4 s − 5) = 4 s( s − t )
PM = 5 PN 8st = 5( s + t )
2 x − y
= 5 y Let P(x, y) be the mid-point of HK,
5 1
2 x − y = ±5 y then x = ( 4 s + 4t ) = 2( s + t ) ..........(1)
2
x − 3 y = 0 or x + 2 y = 0 3
y = ( s − t ) ............................(2)
2
172 Chapter 11 Locus Problems

Eliminating s and t from (1) and (2), we have Exercise 11C (p.283)
(3 x ) − ( 4 y) = [6( s + t )] − [6( s − t )]
2 2 2 2
1. (a) x = t − 2 .............................(1)
9 x − 16 y = 18(8st ) = 18[5( s + t )] = 45 x
2 2
y = 6 − t .............................(2)
16 y 2 = 9 x ( x − 5) From (1), t = x + 2 .............(3)
Substitute (3) into (2),
11. y
y = 6 − ( x + 2)
x+y−4=0
P2(−1, 4)
L1 (b) x = cos θ − 2 .......................(1)
B
P1(3, 2) y = 3 + sin θ ........................(2)
M
From (1), cos θ = x + 2 .......(3)
x
O A From (2), sin θ = y − 3 ........(4)
L2
(3)2 + ( 4)2 ,
1
(a) Slope of L 1 = − cos 2 θ + sin 2 θ = ( x + 2)2 + ( y − 3)2
m
( x + 2)2 + ( y − 3)2 = 1
Slope of L 2 = m
(c) x = t 2 .................................(1)
Equation of L 1 is
y = 4t .................................(2)
1
y − 2 = − ( x − 3) ...................(1) y
m From (2), t = ..................(3)
4
Substitute y = 0 into (1), Substitute (3) into (1),
∴ x = 2m + 3 y
x = ( )2
∴ A is (2 m + 3, 0) . 4
y 2 = 16 x
Equation of L 2 is
1
y − 4 = m( x + 1)........................(2) (d) x = 2(t + ) ........................(1)
t
Substitute x = 0 into (2), 3 1
y = (t − ) .......................(2)
y=4+m 2 t
∴ B is (0, 4 + m) . 1
(1) , x = 4(t 2 + 2 + 2 )
2 2
t
(b) Let M be ( x 1, y 1 ) . 1 x2
t2 + 2 = − 2 .................(3)
2m + 3 t 4
∴ x1 = .......................(3)
2 9 1
(2)2 , y 2 = (t 2 − 2 + 2 ) ...(4)
4+m 4 t
y1 = ........................(4) Substitute (3) into (4),
2
9 1 9 x2
Eliminating m from (3) and (4), we have y 2 = (t 2 − 2 + 2 ) = ( − 2 − 2)
4 t 4 4
4 y1 = 8 + 2 x1 − 3
x2
∴ The equation is 2 x − 4 y + 5 = 0 . 4 y 2 = 9( − 4)
4
9 x 2 − 16 y 2 = 144
12. Let M be (x, y) and B be (p, q).
p + 3⋅2 q + 2⋅2
x= , y= 2. (a) Let P be (x, y).
3 3
 p = 3x − 6  x = 4t − 1 ..........................(1)
∴   y = t + 3 ...........................(2)
q = 3 y − 4 
From (2), t = y − 3 ..............(3)
(3 x − 6 ) 2 + ( 3 y − 4 ) 2
Substitute (3) into (1),
− 3(3 x − 6) + 4(3 y − 4) + 6 = 0
x = 4 ( y − 3) − 1
∴ 3 x 2 + 3 y 2 − 15 x − 4 y + 20 = 0
x − 4 y + 13 = 0
Chapter 11 Locus Problems 173

(b) Let P be (x, y). 4. (a) Case 1 :


y
 x = 4 cos θ ........................(1)
 y = 3 sin θ .........................(2)
 B
x θ
From (1), cos θ = ............(3) 5
4
y P
From (2), sin θ = .............(4) 3
3 θ
x
(3) + ( 4) ,
2 2
O A

x2 y2 A lies on the right of the y-axis,


cos 2 θ + sin 2 θ = +
16 9 B lies on the top of the x-axis.
9 x 2 + 16 y 2 = 144 ∴ P(5 sin θ, 3 cos θ)
(c) Let P be (x, y). Case 2 :
 x = 5 sec θ ........................(1) y
 y = 3 tan θ .........................(2)

B
x
From (1), sec θ = ............(3) θ
5 5
y
From (2), tan θ = ............(4) P
3 3 θ
(3)2 + ( 4)2 , x
A O
x y
sec 2 θ − tan 2 θ = ( )2 − ( )2 A lies on the left of the y-axis,
5 3
x 2 y2 B lies on the top of the x-axis.
1= −
25 9 ∴ P( −5 sin θ, 3 cos θ)
9 x − 25 y = 225
2 2
Case 3 :
(d) Let P be (x, y). y

 x = 1 t 2 ............................(1) A O
x
 2
 y = t
................................(2) 3 θ
Substitute (2) into (1), P
1 2
x= y 5 θ
2
B
y2 = 2 x
A lies on the left of the y-axis,
B lies on the bottom of the x-axis.
3. Let the coordinates of the point be (x, y).
 x = 2t 2.......................(1) ∴ P( −5 sin θ, − 3 cos θ)

 y = 5t .......................(2) Caes 4 :
Substitute (1), (2) into the curve, y

L.H.S. = 2(5t ) = 2(25t ) = 50t


2 2 2
O A
x
R.H.S. = 25(2t ) = 50t = L.H.S.
2 2
θ 3

∴ T h e p o i n t (2t 2 , 5t ) l i e s o n t h e c u r v e P

2 y 2 = 25 x for any real value of t. θ 5

B
174 Chapter 11 Locus Problems

A lies on the right of the y-axis, Revision Exercise 11 (p.284)


B lies on the bottom of the x-axis.
1. Let B be ( x 1, y 1 ) and P be (x, y).
∴ P(5 sin θ, − 3 cos θ)
x12 + y12 = 1 .....................................(1)
(b) Let P be (x, y). 1 1
x = (2 x1 + 1) and y = (2 y1 )
 x = ±5 sin θ ......................(1) 3 3
 y = ±3 cos θ
 ......................(2) 1 3y
x1 = (3 x − 1) and y1 = ..............(2)
x 2 2
From (1), sin θ = ± ..........(3)
5 Substitute (2) into (1),
y 1 1
From (2), cos θ = ± .........(4) (3 x − 1)2 + (3 y)2 = 1
3 4 4
(3)2 + ( 4)2 , (3 x − 1)2 + (3 y)2 = 4
x
sin 2 θ + cos 2 θ = ( )2 + ( )2
y 9x 2 − 6 x + 1 + 9y2 = 4
5 3
3x 2 + 3y 2 − 2 x − 1 = 0
x 2 y2
1= +
25 9
2. Let A be (a, 0), B be (0, b) and P be (x, y).
9 x + 25 y = 225
2 2
1
ab = 25
5. x = cos φ ...........................(1) 2
ab = 50 ....................(1)
y = 2 + cos 2φ ....................(2)
3 2
From (2), x = a, y = b
5 5
y = 2 + 2 cos 2 φ − 1.............(3) 5 5
a = x , b = y ...........(2)
Substitute (1) into (3), 3 2
y = 2 + 2x2 − 1 Substitute (2) into (1),
2x − y + 1 = 0
2 5 5
( x )( y) = 50
3 2
6. x = 2(sec θ + tan θ) .............(1) xy = 12
y = 2(sec θ − tan θ) .............(2)
3. Let A be (a, 0), B be (0, b), the equation of AB is
(1) × (2),
x y
xy = 4(sec θ + tan θ)(sec θ − tan θ) + = 1.
a b
xy = 4(sec 2 θ − tan 2 θ) 3 4
xy = 4 Substitute (3, 4), + = 1
a b
Let P be (x, y), then x = a , y = b .
3t 3 4
7. x = ..........................(1) + =1
1 + t3 x y
3t 2 4 x + 3 y = xy
y= ..........................(2)
1 + t3
(2) y 4. Let P be ( x 1, y 1 ) and Q be (x, y).
, = t ........................(3)
(1) x x1 y1 = 8 ............................(1)
Substitute (3) into (1), 1 1
y
x = x1 , y = y1
3( x ) 2 2
x= y x1 = 2 x , y1 = 2 y ...............(2)
1 + ( x )3
Substitute (2) into (1),
3x 3 y
x= (2 x )(2 y) = 8
x( x 3 + y3 )
xy = 2
x 3 + y 3 = 3 xy
Chapter 11 Locus Problems 175

5. Let P be (x, y) and M be ( −4, y 1 ) , 12


(b) Slope = − = −2
then y = y1 6
4 −1 1
PM = 2 PF Slope of AB = =
3 − ( −3) 2
x + 4 = 2 ( x + 1)2 + y 2 Product of slopes = −1
( x + 4)2 = 4[( x + 1)2 + y 2 ] ∴ The locus is perpendicular to AB.
3 x 2 + 4 y 2 = 12 (c) Substitute B(3, 4),
12(3) + 6( 4) − ( k + 15) = 0
6. (Slope of PA) + (Slope of PO) = 4 k = 36 + 24 − 15 = 45
y y
+ =4 10. (a) L : kx + y = 1 − 2 k
x−5 x
xy + y( x − 5) = 4 x ( x − 5) Substitute (−2, 1),
4 x − 2 xy − 20 x + 5 y = 0
2
L.H.S. = k ( −2) + (1) = 1 − 2 k = R.H.S.
∴ L always passes through (−2, 1) for all
7. Let S be (0, s), T be (t, t) and P(x, y) be the mid- values of k.
point of ST. (b) Slope of L = − k
1 1
Then x = t , y = (s + t ) 1
2 2 Slope of L' =
k
1
t = 2 x , y = (s + t ) Equation of L' is
2
s = 2( y − x ) 1
y − 2 = ( x − 1)
ST = 4 k
ky − 2 k = x − 1
(s − t )2 + t 2 = 4
x − ky = 1 − 2 k
s 2 − 2 st + 2t 2 = 16
(c) Let P(x, y) be a point on the locus.
[2( y − x )]2 − 2[2( y − x )](2 x ) + 2(2 x )2 = 16
4 y 2 − 16 xy + 16 x 2 + 4 x 2 = 16  L: kx + y = 1 − 2 k
 L' : x − ky = 1 − 2 k

20 x 2 − 16 xy + 4 y 2 − 16 = 0
kx + y = x − ky
5 x 2 − 4 xy + y 2 − 4 = 0 k ( x + y) = x − y
x−y
k=
8. x 2 + y 2 = 25 .........................(1) x+y
Let P be ( x 1, y 1 ) and M be ( x 2 , y 2 ) . Substitute k into L,
x−y x−y
Since M is the mid-point of PQ, ( ) x + y = 1 − 2( )
 x = x1 + 2 x+y x+y
 2 2 ( x − y ) x + y ( x + y ) = ( x + y ) − 2( x − y )
∴ 
y1 + 3 x 2 + y 2 + x − 3y = 0
 y2 =
 2
 x1 = 2 x2 − 2
∴  11. Let R(x, y) be a point on the locus.
 y1 = 2 y2 − 3
2(sin θ − cos θ) + (cos θ + sin θ)
Substitute x 1 and y 1 into (1), we have x =
3
(2 x2 − 2)2 + (2 y2 − 3)2 = 25 3 sin θ − cos θ
= .........................................(1)
x2 2 + y2 2 − 2 x2 − 3 y2 − 3 = 0 3
∴ The equation is x 2 + y 2 − 2 x − 3 y − 3 = 0 . 2(sin θ + cos θ) + (cos θ − sin θ)
y =
3
9. (a) Let P be (x, y). 3 cos θ + sin θ
= ..........................................(2)
PA2 − PB2 = k 3
( x + 3)2 + ( y − 1)2 − [( x − 3)2 + ( y − 4)2 ] = k (1)2 , 9 x 2 = 9 sin 2 θ − 6 sin θ cos θ + cos 2 θ......(3)
12 x + 6 y − 15 = k (2)2 , 9 y 2 = 9 cos 2 θ + 6 sin θ cos θ + sin 2 θ......(4)
176 Chapter 11 Locus Problems

(3) + (4), (c) Slope of L 1 = 2


9( x + y ) = 9(sin θ + cos θ) + cos θ + sin θ
2 2 2 2 2 2
1
= 9 +1 Slope of L 3 = −
2
= 10 Equation of L 3 is
9 x 2 + 9 y 2 = 10 1
y − 2 h = − ( x − h)
2
2 y − 4h = − x + h
Enrichment 11 (p.285) x + 2 y − 5h = 0
1. (a) Equation of L 1 , 1
Slope of L 2 =
y − 0 = m( x − 1) 3
y = m( x − 1) Slope of L 4 = −3
Equation of L 2 , Equation of L 4 is
y − 0 = n( x − 6) y − k = −3( x − 3k )
y = n( x − 6) y − k = −3 x + 9k
(b) Q B is equidistant from L 1 and L 2 . 3 x + y − 10 k = 0

(d) P( x 0 , y 0 ) satisfies L 3 and L 4 .


0 − m( 4 ) + m 0 − n( 4 ) + 6 n
∴ =
1 + m2 1 + n2  x 0 + 2 y0 − 5h = 0
3 x + y − 10 k = 0
 0 0
− 3m 1 + n 2 = 2 n 1 + m 2
1
9m 2 (1 + n 2 ) = 4n 2 (1 + m 2 ) ∴ h= ( x 0 + 2 y0 )
5
9m 2 + 5m 2 n 2 − 4n 2 = 0 ...............(1)
1
y k= (3 x 0 + y0 )
(c) From L 1 , m = 10
x −1
y (e) By (b),
From L 2 , n =
x−6 HK
Substitute m and n into (1), = 5h 2 − 10 hk + 10 k 2
y 2 y 2 y 2 y 2 1 1
9( ) + 5( ) ( ) − 4( ) =0 = [ ( x 0 + 2 y0 )2 − ( x 0 + 2 y0 )(3 x 0 + y0 )
x −1 x −1 x − 6 x−6 5 5
9( x − 6)2 + 5 y 2 − 4( x − 1)2 = 0 1
1
+ (3 x 0 + y0 )2 ] 2
5 x 2 − 100 x + 5 y 2 + 320 = 0 10
x 2 + y 2 − 20 x + 64 = 0 1
= { [2( x 0 + 2 y0 )2 − 2( x 0 + 2 y0 )(3 x 0 + y0 )
10
1
2. (a) L 1 : 2 x − y = 0
+ ( 3 x 0 + y0 ) 2
]} 2
Substitute H(h, 2h) into L 1 ,
1
L.H.S. = 2(h) − (2 h) = 0 = R.H.S. = (5 x 0 2 + 5 y0 2 )
10
∴ H is a point on L 1 .
1
L 2 : x − 3y = 0 = ( x 0 2 + y0 2 )
2
Substitute K(3k, k) into L 2 ,
(f) HK = 2
L.H.S. = (3k ) − 3( k ) = 0 = R.H.S. 1
∴ k is a point on L 2 . ( x 0 2 + y0 2 ) = 2
2
x 0 2 + y0 2 = 8
(b) HK = (3k − h)2 + ( k − 2 h)2
= 5h 2 − 10 hk + 10 k 2 The locus is x 2 + y 2 = 8 .
Chapter 11 Locus Problems 177

x = a cos θ ........................(1) Classwork 1 (p.272)


3. (a) 
 = b sin θ ........................(2)
y 1. Let P(x, y) be a point on the locus.
x
From (1), cos θ = ............(3)
a ( x − 1)2 + ( y − 2)2 = ( x + 2)2 + ( y − 3)2
y
From (2), sin θ = ............(4)
b x 2 − 2 x + 1 + y2 − 4 y + 4
(3)2 + ( 4)2 , = x 2 + 4 x + 4 + y2 − 6 y + 9
x y
cos 2 θ + sin 2 θ = ( )2 + ( )2 6x − 2y + 8 = 0
a b
3x − y + 4 = 0
x 2 y2
+ = 1 .......................(*)
a2 b2
2. Let P(x, y) be a point on the locus.
(b) (i) Substitute y = 0 into (*),
x2 ( x − 2)2 + ( y + 3)2 = 4
=1
a2 x 2 − 4 x + 4 + y 2 + 6 y + 9 = 16
x 2 = a2 x 2 + y2 − 4 x + 6y − 3 = 0
x = ±a
∴ A' is (−a, 0) and
A is (a, 0) Classwork 2 (p.272)
Equation of A' P is 1. Let P(x, y) be a point on the locus.
y−0 b sin θ (Slope of PA)(Slope of PB) = −1
=
x + a a cos θ + a
sin θ y −1 y + 2
ay
= ( )( ) = −1
b( x + a) cos θ + 1 x−2 x−5
( y − 1)( y + 2) = −( x − 2)( x − 5)
Coordinates of Q = ( a cos θ, − b sin θ) ( y − 1)( y + 2) + ( x − 2)( x − 5) = 0
Equation of AQ is x 2 + y2 − 7x + y + 8 = 0
y−0 − b sin θ
=
x − a a cos θ − a
ay − sin θ 2. Let P(x, y) be a point on the locus and N is the
= foot of perpendicular from P to the line y − 1 = 0 .
b( x − a) cos θ − 1
PF = PN
 ay = sin θ .................(1)
 b( x + a) cos θ + 1 ( x − 2) + ( y − 3)2 = y − 1
2
(ii) 
ay − sin θ .................(2) ( x − 2)2 + ( y − 3)2 = ( y − 1)2
 =
 b( x − a) cos θ − 1
x 2 − 4 x + 4 + y2 − 6 y + 9 = y2 − 2 y + 1
(1) × (2), x 2 − 4 x − 4 y + 12 = 0
ay ay
[ ][ ]
b( x + a ) b( x − a )
sin θ − sin θ Classwork 3 (p.273)
=( )( )
cos θ + 1 cos θ − 1
1. Let P(x, y) be a point on the locus.
a2 y2 − sin 2 θ
= PA2 + PB2 = 25
b 2 ( x 2 − a 2 ) cos 2 θ − 1
x 2 + ( y − 3)2 + x 2 + ( y + 2)2 = 25
a2 y2
=1 2 x 2 + 2 y 2 − 2 y = 12
b2 x 2 − a2b2
x 2 + y2 − y − 6 = 0
x 2 y2
− =1
a2 b2
178 Chapter 11 Locus Problems

2. Let P(x, y) be a point on the locus. y


From (1), t = ......................................(3)
−2 1 x
Substitute (3) into (2),
1 3 4
=6 y y
2 x y ( )y = − x +
x x
−2 1 y2 = − x 2 + y
1 x 2 + y2 = y
[( −8 + 3 y + x ) − (3 + 4 x − 2 y)] = ±6
2
−11 + 5 y − 3 x = ±12
−11 + 5 y − 3 x = 12 or −11 + 5 y − 3 x = −12 Classwork 6 (p.283)
3 x − 5 y + 23 = 0 or 3x − 5y − 1 = 0  x = t 2 + 3t ........................(1)

1. (a) 
 y = t 2 − 1 ........................(2)

Classwork 4 (p.275) From (2), t 2 = y + 1 ............(3)
Let P be (x, y). t = ± y + 1 ........(4)
PA − PB = 2 Substitute (3) and (4) into (1),
( x + 3) + y − ( x − 3) + y = ±2
2 2 2 2 x = y +1± 3 y +1
( x + 3)2 + y 2 = ±2 + ( x − 3)2 + y 2 x − y − 1 = ±3 y + 1
( x + 3) + y
2 2 ( x − y − 1)2 = 9( y + 1)
x 2 + y 2 − 2 x + 2 y − 2 xy + 1 = 9 y + 9
= 4 + ( x − 3)2 + y 2 ± 4 ( x − 3)2 + y 2
x 2 + y 2 − 2 xy − 2 x − 7 y − 8 = 0
3 x − 1 = ± ( x − 3)2 + y 2
(3 x − 1)2 = ( x − 3)2 + y 2 x = 4 sin θ + 1 ..............................(1)
(b) 
9x − 6x + 1 = x − 6x + 9 + y
2 2 2
 y = 2 cos θ − 3 .............................(2)
8x 2 − y2 = 8 1
From (1), sin θ = ( x − 1) .............(3)
4
1
From (2), cos θ = ( y + 3) .............(4)
Classwork 5 (p.277) 2
(3)2 + ( 4)2 ,
1. Let the coordinates of M be (x, y)
1 1
and the coordinates of B be ( x 1, y 1 ) . sin 2 θ + cos 2 θ = ( x − 1)2 + ( y + 3)2
16 4
1
x = (3 + x1 ) 16 = ( x − 1)2 + 4( y + 3)2
2 x 2 + 4 y 2 − 2 x + 24 y + 21 = 0
x1 = 2 x − 3 ................................(1)
1
y= (2 + y1 ) 2. Let P be (x, y).
2
y1 = 2 y − 2 ................................(2)  x = sin θ − 1........................................(1)
 y = sin θ + cos θ ..................................(2)

Since B satisfies the curve,
From (1), sin θ = x + 1..........................(3)
x12 + y12 + 2 x1 − y1 = 0..............(3)
sin 2 θ = x 2 + 2 x + 1
Substitute (1) and (2) into (3), cos 2 θ = − x 2 − 2 x
(2 x − 3) + (2 y − 2) + 2(2 x − 3) − (2 y − 2) = 0
2 2
cos θ = ± − x 2 − 2 x ..............(4)
4 x − 12 x + 9 + 4 y − 8 y + 4 + 4 x − 6 − 2 y + 2 = 0
2 2
Substitute (3) and (4) into (2),
4 x 2 + 4 y 2 − 8 x − 10 y + 9 = 0
y = x + 1 ± −x2 − 2x

2. Let P(x, y) be a point on the locus. y − x − 1 = ± −x2 − 2x


Equation of OM : y = tx .................(1) x 2 + y 2 + 2 x − 2 y − 2 xy + 1 = − x 2 − 2 x
2 x 2 + y 2 − 2 xy + 4 x − 2 y + 1 = 0
Equation of CN : ty = − x + t ...........(2)